Rātchaphongsāwadān Krung Kamphūchā (Great Collections Microfilming Project. John M. Echols Collection., 1970)
Translations of Khmer royal historical chronicles from ancient times to 1865 A.D., covering history of Cambodia and relations with Thailand, selected and edited by Fine Arts Dept. of Thailand.